2022
DOI: 10.3389/fmicb.2022.1057202
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of finafloxacin in a murine model of inhalational glanders

Abstract: Burkholderia mallei, the causative agent of glanders, is principally a disease of equines, although it can also infect humans and is categorized by the U.S. Centers for Disease Control and Prevention as a category B biological agent. Human cases of glanders are rare and thus there is limited information on treatment. It is therefore recommended that cases are treated with the same therapies as used for melioidosis, which for prophylaxis, is co-trimoxazole (trimethoprim/sulfamethoxazole) or co-amoxiclav (amoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Since glanders is primarily a respiratory or cutaneous disease [7], a switch was decided, thus altering the route of infection. The aerosol infection model is feasible [23,30] but can represent a risk to laboratory workers, as cases of human glanders have been related to this occupation [31]. Moreover, it depends on using specific apparatus, and depending on the equipment and technique used to generate the aerosol, it could be hard to generate a previous quantification of the inoculated CFU.…”
Section: Discussionmentioning
confidence: 99%
“…Since glanders is primarily a respiratory or cutaneous disease [7], a switch was decided, thus altering the route of infection. The aerosol infection model is feasible [23,30] but can represent a risk to laboratory workers, as cases of human glanders have been related to this occupation [31]. Moreover, it depends on using specific apparatus, and depending on the equipment and technique used to generate the aerosol, it could be hard to generate a previous quantification of the inoculated CFU.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous vaccine (once) and Trimethoprim-sulphadiazine (20 mg/kg B/W P/O) for 1 month alter the disease course if given to infected horses (Al-Ani and Roberson 2007). A study in mice showed that Finafloxacin controls B. mallei at the organ level and also controls the signs which are going to develop (Barnes et al 2022). Bacteria are sensitive to co-Trimoxazole, Danofloxacin, Norfloxacin, and Chloramphenicol.…”
Section: Treatmentmentioning
confidence: 99%